The Importance of Interdisciplinary Relations in the Development of Professional Competence of Technology Teacher - Abdurasulova Ominahon Jakbarali qizi (Periodica Journal, 2022)
In this article, any science occurs under the influence of other sciences close to it and develops together with them. The importance of the use of interdisciplinary links in the teaching of science in schools, colleges and universities was highlighted.
Keywords: Integration; Relevance; Lesson; Practice